2023
DOI: 10.3390/molecules28031239
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloid Profile in Wild Autumn-Flowering Daffodils and Their Acetylcholinesterase Inhibitory Activity

Abstract: Amaryllidaceae alkaloids are secondary metabolites with interesting medicinal properties. Almost every Narcissus species can synthesize them and constitute an excellent source for their isolation and study. Several Amaryllidaceae alkaloids have shown acetylcholinesterase inhibitory activities and are a promising tool for treating cholinergic disorders such as Alzheimer’s disease (AD). Indeed, three of the four palliative treatments approved for AD are acetylcholinesterase (AChE) inhibitors and one of them, gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…No information about the alkaloid profile of the species N. minor and N. nevadensis has been found in the literature. Regarding the alkaloid composition and anti-cholinesterase activity of certain species not listed in Table 3, Lisa-Molina and co-workers [6] evaluated the alkaloid profiling of ten samples of Narcissus, totaling nine different species (N. obsoletus, N. deficiens, N. serotinus, N. cavanillesii, N. viridiflorus, N. elegans, N. papyraceus, N. bulbocodium, N. blancoi) collected in Spain [6]. The authors detected thirty alkaloids among these samples, with two of them not being identified [6].…”
Section: Samplesmentioning
confidence: 99%
See 3 more Smart Citations
“…No information about the alkaloid profile of the species N. minor and N. nevadensis has been found in the literature. Regarding the alkaloid composition and anti-cholinesterase activity of certain species not listed in Table 3, Lisa-Molina and co-workers [6] evaluated the alkaloid profiling of ten samples of Narcissus, totaling nine different species (N. obsoletus, N. deficiens, N. serotinus, N. cavanillesii, N. viridiflorus, N. elegans, N. papyraceus, N. bulbocodium, N. blancoi) collected in Spain [6]. The authors detected thirty alkaloids among these samples, with two of them not being identified [6].…”
Section: Samplesmentioning
confidence: 99%
“…Regarding the alkaloid composition and anti-cholinesterase activity of certain species not listed in Table 3, Lisa-Molina and co-workers [6] evaluated the alkaloid profiling of ten samples of Narcissus, totaling nine different species (N. obsoletus, N. deficiens, N. serotinus, N. cavanillesii, N. viridiflorus, N. elegans, N. papyraceus, N. bulbocodium, N. blancoi) collected in Spain [6]. The authors detected thirty alkaloids among these samples, with two of them not being identified [6]. According to their results, the lycorine-type skeleton was the most diverse group detected among the samples, with these structures being observed in all of the species, except in N. viridiflorus and N.bulbocodium [6].…”
Section: Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Phytochemical components in plants can facilitate treatment with a synergistic effect [ 31 , 38 ]. AD is a multifaceted neurodegenerative disease that arises and is characterized by changes in memory, behavior, reasoning, emotions, and abstract thinking [ 39 ]. The cholinergic hypothesis, which best explains the symptoms and pathophysiology of the disease, is accepted as one of the main hypotheses.…”
Section: Introductionmentioning
confidence: 99%